2012
DOI: 10.1021/jo301846a
|View full text |Cite
|
Sign up to set email alerts
|

NMR and Computational Studies of the Configurational Properties of Spirodioxyselenuranes. Are Dynamic Exchange Processes or Temperature-Dependent Chemical Shifts Involved?

Abstract: Spirodioxyselenurane 4a and several substituted analogs revealed unexpected (1)H NMR behavior. The diastereotopic methylene hydrogens of 4a appeared as an AB quartet at low temperature that coalesced to a singlet upon warming to 267 K, suggesting a dynamic exchange process with a relatively low activation energy. However, DFT computational investigations indicated high activation energies for exchange via inversion through the selenium center and for various pseudorotation processes. Moreover, the NMR behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…It is due to the diastereotopic nature of the methylene protons. A similar pattern has been reported by Back and coworkers for 9a [35]. The 77 Se-NMR spectrum of compound 22 exhibits a signal at 908 ppm.…”
Section: Resultssupporting
confidence: 86%
“…It is due to the diastereotopic nature of the methylene protons. A similar pattern has been reported by Back and coworkers for 9a [35]. The 77 Se-NMR spectrum of compound 22 exhibits a signal at 908 ppm.…”
Section: Resultssupporting
confidence: 86%
“…Typical Procedure for the Preparation of Allyl Aryl Selenides: [4-Methoxy-2-(prop-2-en-1-ylselanyl)phenyl]methanol (20). Diselenide 14 (200 mg, 0.463 mmol) was dissolved in 18 mL of THF−ethanol (5:1) and cooled to 0 °C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…room temperature and, unexpectedly, split into new AB quartets upon further heating, as a result of temperature-dependent chemical shifts of the exo and endo protons. 20,21 Chart 1 Scheme 2…”
mentioning
confidence: 99%
“…This results in the observed singlet, followed by divergence of shifts at still higher temperatures to regenerate an ew set of doublets. [51] While several of the cyclic seleninates and spiroselenuranes describeda bove have improveda ctivity compared to ebselen in the indicated assays,m ost display equally poor solubility in water.I no rder to improves olubility,s elenides 36 and 38 were prepared, representing the reduced form of spiroselenuranes 37 and 39,r espectively. [52,53] These compounds retain one arylseleniumb ond in order to resist metabolic conversion into toxic inorganic species, but display much improved solubility properties.…”
Section: Spirodioxyselenuranesmentioning
confidence: 99%
“…Computational studies revealed that as the temperature is increased, higher vibrational levels become populated, which changes the chemical shifts of the diastereotopic hydrogens, such that the shifts converge around room temperature. This results in the observed singlet, followed by divergence of shifts at still higher temperatures to regenerate a new set of doublets …”
Section: Spirodioxyselenuranesmentioning
confidence: 99%